Foundation Flight, Expulsion, Reconciliation – German Government Response to the Federation of Expellees’ History Interpretation Policy (Economic and Political Thought, 2013)
The publication is aimed at demonstrating the political dimension of thediscussion on the establishing of the Foundation ‘Flight, Expulsion, Reconciliation’.The article is also an attempt to answer a question about the influenceof that debate on the present-day relations between Poland and Germany.The presented polemic over the issue ends at the turn of the years 2009/2010.It was a period when the most important decisions in connection with theshape of the foundation, the German government’s response to the Federationof Expellees’ history interpretation policy, were made. The Act passedby Bundestag created the basis for the establishment of a new institution,was an expression of a wide compromise between the two biggest parliamentfactions of the Federal Republic (CDU/CSU and SPD) and depicted theactual powers in the German parliament. The unquestionable success ofBund der Vertriebenen (BdV) was the fact that, in spite of the long-lastingopposition, especially on the part of Polish politicians, the Foundation Boardhas six seats for the members of BdV as a compensation for the Federationof Expellees’ Chairperson’s resignation to be a member of that body. Thisway the representatives of the German expellees gained an opportunity tohave a direct influence on the future conception of the museum, although toa limited extent. The author, with the use of a comparative method, analyzesthe stands of particular representatives of the German political parties onthat issue. Due to the topicality of the issue, press publications are the mainsources. Source materials in the German language, including the Bundestagplenary sessions protocols and the Federation of Expellees’ press releases,also played an important role.